Laparoscopic Adrenalectomy for Pheochromocytoma - Intraoperative Cardiac Arrest and Cardiopulmonary Resuscitation in Lateral Position: A Case Report (BIRDEM Medical Journal, 2019)
Anaesthetic management of patients with large adrenal gland tumor pheochromocytoma is a challenge to the anesthesiologist, due to perioperative uncontrolled blood pressure, risk of arrhythmias and sudden cardiac arrest. Therefore, preoperative assessment and appropriate anaesthetic management are important in patients with pheochromocytoma. Laparoscopic adrenalectomy for Pheochromocytoma offers some technical advantages owing to its improved ability to visualize the contiguous anatomy and its relationship to the adrenal tumor. The decreased manipulation of the tumor during dissection of the adrenal gland has been espoused as another benefit of the laparoscopic approach. The decreased release of catecholamines and the resultant attenuation in haemodynamic liability has been a purported advantage of the laparoscopic approach.1,2,3,4 This is a case report of successful anaesthetic management of a patient with pheochromocytoma undergoing laparoscopic adrenalectomy using combined general and epidural anaesthesia the patient who developed intraoperative cardiac arrest and complete recovery after given lateral position CPR.Birdem Med J 2019; 9(2): 165-169